Postpartum depression in Vietnam: a scoping review of symptoms, consequences, and management - Huyen Thi Hoa Nguyen; Phuong Anh Hoang; Thi Kim Ly Do; Andrew W. Taylor-Robinson; Thi Thanh Huong Nguyen (BMC Women's Health, 2023)
Abstract Background Postpartum depression (PPD) is a major health issue that can affect both mothers and their newborn children. In Vietnam, approximately 20% of mothers suffer from PPD. However, there is a lack of synthesized evidence regarding the case management of PPD in the Vietnamese context. A review of early symptoms, consequences, and management strategies of PPD will help to inform best practices to reduce complications and shorten the recovery time after parturition. Methods This scoping review aims to analyze and synthesize the findings of studies on PPD examining the symptoms, consequences, and management strategies among Vietnamese women. MEDLINE, CINAHL, PubMed, ScienceDirect, EBSCOHost, Google Scholar, and a networked digital library of projects, theses, and dissertations published between 2010 and 2022 in Vietnam were accessed following search terms including “Vietnam”, “depression”, “postpartum”, “symptom/experience”, “consequence”, and “management”. Findings The most-reported symptoms were sadness, tiredness, the feeling of being ignored, lack of interest in the baby, reduced appetite, and sleep disturbance. The recognized consequences were child stunting and slow growth, without mentioning its long-term effects on mothers. Our findings indicated that PPD in Vietnam has not been sufficiently managed; mothers tend to seek help from ‘fortune-tellers’ or ‘word-of-mouth’ practices rather than from evidence-based modern medicine. Conclusion This scoping review provides an initial stage of PPD symptoms, consequences, and management along with facilitating an interventional program to support this vulnerable group of women. A large survey of Vietnamese mothers' symptoms, effects, and management strategies is needed.